2020
DOI: 10.1111/dth.14661
|View full text |Cite
|
Sign up to set email alerts
|

MOHS micrographic surgery for head and neck nonmelanoma skin cancer: An approach for ENT surgeons

Abstract: Surgery is the main approach for skin cancer, with Mohs micrographic surgery (MMS) allowing the highest cure rates, best esthetics and superior functional outcomes. Ear, nose, and throat (ENT) surgeons are often challenged with patients presenting skin cancer, needing appropriate expertise to its adequate management. This paper highlights the most important aspects of MMS, enabling ENT surgeons to become familiar with its fundamental aspects. A review of the literature was performed, concomitantly presenting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These cases were specifically guided by the ENT consultation for MMS because they required tissue saving, with the need for accurate margin assessment to perform simultaneous reconstruction. 4 The most frequent locations of the MMS treated cBCCs were the nose (13/32, 40.6%) and the eyelids (9/32, 28.1%). None of these cBCCs recurred.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These cases were specifically guided by the ENT consultation for MMS because they required tissue saving, with the need for accurate margin assessment to perform simultaneous reconstruction. 4 The most frequent locations of the MMS treated cBCCs were the nose (13/32, 40.6%) and the eyelids (9/32, 28.1%). None of these cBCCs recurred.…”
Section: Resultsmentioning
confidence: 93%
“… 2 Surgical modality is based on the risk assessment of cBCC with standard surgical excision reserved for low-risk tumors and Mohs micrographic surgery (MMS) for the excision of tumors in esthetically and functionally sensitive areas. 3 , 4 Because surgery is the treatment of choice, surgical margins are an important issue, with a need for a compromise between tumor eradication and acceptable cosmetic outcomes. 4 A meta-analysis performed by Gulleth et al 5 has shown that a 3-mm surgical margin can be safely used for nonmorpheaform cBCC to attain 95% cure rates for tumors 2 cm or smaller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, repeated intraoperative inspection of the resection margin can ensure complete tumor removal, in order to significantly reduce the postoperative recurrence rate. 14 For the ala nasi, periorbital, eyelid margin, and medial canthus areas, especially when there are recurrent facial tumors with unclear clinical boundaries or tumors with an invasive growth pattern on histopathology (eg, morphea-like basal-cell carcinoma), Mohs micrographic surgery has obvious advantages. However, this surgery also has its shortcomings.…”
Section: Discussionmentioning
confidence: 99%